Ruthenium(III) Catalysed Oxidation of Aliphatic Amines by N-Bromosuccinimide in Perchloric Acid Medium - Saxena, Rashmi; Upadhyay, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of ruthenium(III) catalysed oxidation of aliphatic amines viz. ethylamine, diethylamine and triethylamine by N-bromosuccinimide (NBS) have been investigated in perchloric acid medium and in presence of mercuric acetate. The order of reaction in NBS varies between one and two. A first order dependence of rate with respect to each substrate and catalyst and an inverse first order dependence of rate with respect to acid has been observed. A retarding effect of succinimide and acetic acid on the rate of reaction was also observed in each case. A suitable mechanism is proposed and discussed.